O9.7. TECHNOLOGY ASSISTED RELAPSE PREVENTION PROGRAM REDUCES HOSPITALIZATION IN SCHIZOPHRENIA PATIENTS AT HIGH RISK FOR RELAPSE. (18th May 2020) - Schooler, Nina; Robinson, Delbert; Marcy, Patricia; Homan, Philipp; Achtyes, Eric; Kane, John M
Abstract: Background: Psychiatric hospitalization is a major driver of cost in the treatment of schizophrenia. During the first six months after a hospitalization, patients are at increased risk for return to the hospital. Targeting treatment during this period may be especially valuable. Mobilizing a range of treatment enhancements using both smart phones and computers to support patients by individualizing treatment to specific needs may be especially beneficial. The Improving Care Reducing Cost (ICRC) program sought to determine whether a novel, multicomponent, and technology-enhanced approach to relapse prevention in outpatients following a psychiatric hospitalization could reduce days spent in a hospital after discharge. Methods: The ICRC study was a quasi-experimental clinical trial in outpatients with schizophrenia conducted between February 2013 and April 2015 at 10 sites in the US that provide both in and outpatient. Data were obtained from 89 participants who received usual relapse prevention services, followed by a second cohort of 349 participants who received technology-enhanced relapse prevention program. Both groups were followed for 6 months. Patients were between 18 and 60 years old; had a diagnosis of schizophrenia, schizoaffective disorder, or psychotic disorder not otherwise specified; and were currently hospitalized or had been hospitalized within the past 30 days at consent. The first cohort received usual care; the second cohort received the Health Technology Program (HTP) a technology-enhanced relapse prevention program. HTP included medication treatment guided by a computer decision support system for the prescriber, a smartphone application for patients that supported medication adherence and other coping strategies, a web-based patient and family psycho-educational intervention, and web-accessed cognitive behavioral therapy for paranoia and hallucinations. A mental health technology coach provided technical support, and developed a personalized, structured, relapse prevention plan with each participant that identified individual relapse precipitants and determined which HTP components should be employed to address them. All patients received computers and Android smartphones to insure access to the interventions. Days spent in a psychiatric hospital during 6 months after discharge was assessed. The Heinrichs Carpenter Quality of Life Scale was completed at baseline and six months. Results: The study included 438 patients. Control participants (N = 89; 37 females) were enrolled first and received usual care for relapse prevention, and followed by 349 participants (128 females) who received the HTP. Days of hospitalization were reduced by 4 days (Mean days: b = -4.25, 95% CI: -8.29; -0.21, P = 0.039) during follow-up in the intervention condition compared to control. Finally, using Heinrichs Carpenter Quality of Life total score at month 6 as an outcome, we found no significant effect of HTP (β = 0.02, t (345) = 0.43, P = 0.668). Discussion: Recently hospitalized patients with schizophrenia who received an integrated technology informed relapse prevention program (HTP) experienced fewer days in the hospital compared to those who received usual care in the six months following their discharge. Given the high patient burden and costs of even a single day spent in a psychiatric hospital, estimated at $1358 per day based on inflation adjusted results from a recent study, our findings imply total savings in psychiatric inpatient expenditures of $5772 during the first 6 months after discharge on average. However, reduction in hospitalization days did not result in a parallel improvement in functioning as assessed by the Quality of Life Scale. Although the control and experimental cohorts were comparable in many characteristics, the quasi–experimental design represented by sequential cohorts rather than a true concurrent randomized controlled trial represents a limitation. The results of the study suggest that technology enhanced treatments that are tailored to patient needs can be implemented in a range of clinical settings in the US to patients at high risk of hospitalization and that the intervention can reduce subsequent hospitalization days. Future research should address limitations in the current study design and will benefit from the development of technology applications that can be available on a single flexible platform.